Inovasi Strategi Sport Education Model (SEM) pada Cabang Olahraga Sepak Bola untuk Meningkatkan Literasi Fisik dan Literasi Sosial - Hardika Musfrianto; Ainul Fikri; Imam Mujahid; Saiful Arzan Haq; Nurul Fakhirah Sultan; Reskiani Randa Parantean; Poppy Elisano Arfanda; Juhanis; Anita Rahman (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to examine the innovative application of the Sport Education Model (SEM) in football teaching to enhance students’ physical literacy and social literacy. The research method employed is a literature review using a descriptive qualitative approach. Data collection was conducted through the search and selection of scientific articles, books, and research publications relevant to SEM, physical education, physical literacy, and social literacy. Data analysis was conducted using content analysis, comprising the stages of data reduction, data presentation, and drawing conclusions. The findings indicate that the implementation of SEM is capable of creating a more contextual and meaningful learning experience through competition-season-based learning organisation, the formation of consistent teams, the allocation of social roles, and structured reflective evaluation. This model has been shown to improve students’ playing skills, understanding of game tactics, motivation to participate in physical activities, as well as their ability to cooperate and communicate socially. Consequently, the Sport Education Model has the potential to become an effective learning innovation in optimally supporting the development of students’ physical and social literacy within physical education.